STUDY MOUNT PROSPERITY OF FARMER OF PADDY RICE FIELD IN KENAGARIAN RANAH PANTAI CERMIN DISTRICT OF SANGIR BATANG HARI SUB-PROVINCE SOLOK SOUTH - EMASARI, YULIA; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Thesiwati, SP., M.Si, Aslan Sari (STKIP PGRI Sumbar, 2014)
Abstracts This Research aim to for the description of Study Mount Prosperity of Farmer of Paddy rice field in Kenagarian Ranah Pantai cermin District Of Sangir Batang Hari Sub-Province of Solok South, seen of 1) requirement of clothing, 2) requirement of food and 3) requirement of board. This Research method is descriptive, this research population is all family head farmer of rice field paddy who live in Coastal Kenagarian Ranah Pantai cermin District Of Sangir Batang Hari Sub-Province of Solok South amounting to 58 KK.. Data collecting by using enquette, with Technique Analysis, using percentaSe formula and Storey Level Attainment Of Responder ( TCR). Result of research cover 1) Requirement of family clothing farmer of rice field paddy in Coastal Kenagarian Ranah Pantai cermin District Of Sangir Batang Hari Sub-Province of Solok South in obtaining mean score 2,18 with storey level attainment of responder equal to 54,59% staying in bad category 2) Requirement of family food farmer of rice field paddy in Coastal Kenagarian Ranah Pantai cermin District Of Sangir Batang Hari Sub-Province of Solok South in obtaining mean score 2,58 with storey level attainment of responder equal to 64,5% staying in unfavourable category 3) Requirement of family board farmer of rice field paddy in Coastal Kenagarian Ranah Pantai cermin District Of Sangir Batang Hari Sub-Province of Solok South in obtaining mean score 3,13 with storey level attainment of responder equal to 78,28% staying in good enough category.